2016
DOI: 10.1891/1058-1243.25.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Related Anxiety in Women Who Conceive Via In Vitro Fertilization: A Mixed Methods Approach

Abstract: The process of in vitro fertilization (IVF) causes anxiety, but it is unclear whether this anxiety continues into pregnancy and affects childbirth preparation. This study administered the pregnancy-related anxiety measure to 144 women during their second trimester. Anxiety scores were slightly higher among IVF compared to non-IVF pregnant women. Thirty-one participants provided narrative data about their pregnancy-specific anxiety. Themes emerged from qualitative analysis related to anxiety about the health of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…45 In cases of fetal complications, there may be concerns about the baby being harmed during delivery, and worries about being separated from the baby after birth can also cause anxiety in the perinatal period. 46,47 Our study obtained similar | 999…”
Section: Discussionsupporting
confidence: 66%
“…45 In cases of fetal complications, there may be concerns about the baby being harmed during delivery, and worries about being separated from the baby after birth can also cause anxiety in the perinatal period. 46,47 Our study obtained similar | 999…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have shown pregnancy specific anxiety in IVF mothers, such as anxiety about the survival and normality of their unborn babies and damage to their babies during childbirth. 10,25 To the best of our knowledge, this study is the first to explore the women's experiences of assisted conception and ART providers' perception of their patients' experiences in the Indian setting. The findings of the study have led to the understanding that the previous negative experiences in conception affect the way women experience their pregnancy achieved through assisted conception.…”
Section: Discussionmentioning
confidence: 99%
“….. I don't think I'll relax till he/she is here' (Stevenson et al 2016). Older maternal age was also a factor affecting women's anxiety about the health of their unborn baby; 'My age is a big factor in the odds of having a baby with a genetic disorder' (Stevenson et al 2016).…”
Section: Theme 4: Social Norms and Expectationsmentioning
confidence: 99%